South End Shout Boston's Forgotten Music Scene in the Jazz Age - House, Roger (Lever Press, 2023)
South End Shout: Boston's Forgotten Music Scene in the Jazz Age details the power of music in the city's African American community, spotlighting the era of ragtime culture in the early 1900s to the rise of big band orchestras in the 1930s. This story is deeply embedded in the larger social condition of Black Bostonians and the account is brought to life by the addition of 20 illustrations of musicians, theaters, dance halls, phonographs, and radios used to enjoy the music. South End Shout is part of an emerging field of studies that examines jazz culture outside of the major centers of music production. In extensive detail, author Roger R. House covers the activities of jazz musicians, jazz bands, the places they played, the relationships between Black and white musicians, the segregated local branches of the American Federation of Musicians (AFL-CIO), and the economics of Boston's music industry. Readers will be captivated by the inclusion of vintage local newspaper reports, classified advertisements, and details of hard-to-access oral history accounts by musicians and residents. These precious documentary materials help to understand how jazz culture evolved as a Boston art form and contributed to the national art form between the world wars. With this book, House makes an important contribution to American studies and jazz history. Scholars and general readers alike who are interested in jazz and jazz culture, the history of Boston and its Black culture, and 20th century American and urban studies will be enlightened and delighted by this book.